Ethical Climate(s), Organizational Identification, and Employees’ Behavior - Teresi, Manuel; Pietroni, Davide Dante; Barattucci, Massimiliano; Giannella, Valeria Amata; Pagliaro, Stefano (Frontiers in Psychology, 2019)
Ethical climate defines what is correct behavior and how ethical issues should be handled within organizations. For this reason, it is central to organizational life. We relied on the Social Identity Approach to compare the effects of two specific ethical climates – an ethical climate of self-interest vs. friendship – on employees’ reactions. In two scenario-based experiments (N1 = 152 and N2 = 113), participants were asked to imagine themselves working in an organization described either as characterized by a friendship or a self-interest ethical climate. They completed measures of identification, commitment, perceived organizational morality, turnover intention, recommendation and the minimum wage they would accept to work for that organization. An ethical climate of friendship predicted better employees’ attitudes and behavioral intentions, and these were mediated by identification with, and commitment to, the organization. In Study 2 participants were less willing to move from an organization characterized by an ethical climate of friendship to a company characterized by an ethical climate of self-interest than vice versa, and asked for more money to accept this new job offer. Results, which confirmed that organizational identification and commitment represent key factors in organizational life, are discussed in terms of practical interventions that promote pro-organization behavior.